Sustainable Analysis of the Use of Organic Fertilizer in Rice Fields in Deli Serdang Regency - Supriadi Surbakti; Octasella Ainani As'ad (Journal of Agriculture, 2026)
This study aims to analyze the sustainability of organic fertilizer use in lowland rice crops in Deli Serdang Regency, North Sumatra. The study focused on the agronomic, ecological, and socio-economic aspects of the application of organic fertilizer as a substitute or supplement to inorganic fertilizers. The study was conducted using a descriptive analytical approach using survey methods and literature studies in rice fields in six sub-districts, rice production centers in Deli Serdang Regency. Data were collected through structured interviews with 120 lowland rice farmers and field observations during the 2023/2024 planting season. The results showed that consistent use of organic fertilizers increased soil organic carbon content from an average of 1.2% to 2.4% after three consecutive planting seasons. Lowland rice productivity on land applied with combined organic fertilizers reached 6.2 tons/ha of dry grain (GKG), higher than on conventional land with an average production of 5.4 tons/ha of dry grain (GKG). Sustainability analysis showed that the application of organic fertilizers had a positive impact on soil quality, reduced greenhouse gas emissions, and increased farmers' income by 18.5% in the medium term. The main obstacles identified include limited availability of organic raw materials, relatively high initial costs, and farmers' lack of technical knowledge in organic fertilizer production and application. Integrated government policy support and ongoing training programs are needed to encourage widespread adoption of organic fertilizer in Deli Serdang Regency.